Caracterización morfológica y organoléptica de variedades potenciales de chirimoya (Annona cherimola Mill.) en poblaciones del Cantón Paltas, Provincia de Loja - Torres Padilla, Angie Esthela (2024)
The cherimoya (Annona cherimola Mill.) is a species of major international commercial importance. It is native to Ecuador, where a high diversity stands out, mainly concentrated in Loja Province. However, cherimoya is considered a secondary and minor crop for most producers, which is why they do not provide agronomic care, dominating the collection in natural forests or trees from family gardens; there is no intensification of cultivation due mainly to lack of knowledge about its management and the potential varieties that may exist in the area. This research aimed to identify the varieties of cherimoya (Annona cherimola Mill.) with productive potential in populations of the canton of Paltas, Province of Loja. A total of 20 individuals were characterized and distributed within three locations, using the Biodiversity International and CHERLA descriptor and parameters to measure organoleptic characteristics. For statistics analysis, different proceedings of multivariate analysis were used. The results show that, according to the quantitative and qualitative characteristics at the individual and fruit level, the individuals evaluated in the Paltas canton are classified into four groups, where the PTA 02 and PTA 07 individuals stand out, both belonging to the Lisa variety; regarding the organoleptic variables, considering quality parameters and fruit marketing. The individuals PTA 06 and PTA 11 stood out, belonging to the Impresa and Mamillata varieties, respectively. The individuals highlighted above, PTA 02, PTA 07, PTA 06, and PTA 1 are from Tunaspamba town in the Paltas canton. It ́s concluded that there are cherimoya potential varieties in Paltas canton with traits for the production of the crop.